m6A-mRNA Methylation Regulates Gene Expression and Programmable m6A Modification of Cellular RNAs With CRISPR-Cas13b in Renal Cell Carcinoma - Gan, Ying; Li, Aolin; Liu, Jun; Wang, Xiaofei; Zhang, Zhenan; Li, Qinhan; Ye, Xiongjun; Yao, Lin; Zhang, Qian (Frontiers in Genetics, 2022)
Background: N6-methyladenosine (m6A) is the most extensive messenger RNA modification. Despite recent advances in the biological roles of m6A, its role in the development and progression of renal cell carcinoma (RCC) remains unclear. Methods: In this study, we gained the transcriptome-wide m6A profile and gene expression pattern in RCC and paired adjacent peritumoral tissues by meRIP-seq and RNA-seq. m6A modifications of mRNAs were validated by meRIP-qPCR in tissues, and targeted methylation or demethylation was validated by using a CRISPR-Cas13b-based tool in RCC cell lines. Results: Our findings showed that there were 13,805 m6A peaks among 5,568 coding gene transcripts (mRNAs) in adjacent tissues and 24,730 m6A peaks among 6,866 mRNAs in tumor tissues. Furthermore, m6A modification sites were usually located in the coding sequences (CDS), and some near the start and stop codons. Gene Ontology analysis revealed that coding genes had differential N6-methyladenosine sites and were enriched in kidney development and cancer-related signaling pathways. We also found that different levels of m6A modifications could regulate gene expression. Conclusion: In summary, our results provided evidence for studying the potential function of RNA m6A modification and m6A-mediated gene expression regulation in human RCC.